Розробка та використання сніферу як засобу забезпечення безпеки ТСР з’єднань - Шаров, Сергій Володимирович; Лубко, Дмитро Вікторович; Лубко, Дмитрий Викторович; Lubko, Dmytro; Шаров, Сергей Владимирович; Sharov, Sergii (Харківський університет Повітряних Сил імені Івана Кожедуба, 2017)
UK: У статті повідомляється про розробку програмного засобу для перехоплення та аналізу вихідних TCP з’єднань (сніферу), описуються етапи його розробки та вимоги до використання, подається коротка інструкція користувача. Функціональні можливості розробленого програмного засобу дозволяють автоматизувати окремі функціональні обов’язки системного адміністратора. Також розроблений сніфер надає можливість контролювати весь процес передачі даних в довільному 32-розрядному програмному забезпеченні. Програмний засіб має зручний та простий користувальницький інтерфейс, який дозволяє використовувати його навіть початківцям. RU: В статье сообщается о разработке программного средства для перехвата и анализа исходных TCP соединений (снифера), описываются этапы его разработки и требования к использованию, дается краткая инструкция пользователя. Функциональные возможности разработанного программного средства позволяют автоматизировать отдельные функциональные обязанности системного администратора. Также разработанный снифер позволяет контролировать весь процесс передачи данных в произвольном 32-разрядном программном обеспечении. Программное средство имеет удобный и простой пользовательский интерфейс, который позволяет использовать его даже начинающим. EN: The article focuses on the development of a software tool for intercepting and analyzing outbound TCP connections as one of the means of providing information security in the Internet. It is noted that cybersecurity is one of the main issues of the state level, as the loss of important information can lead to negative economic, political consequences, etc. There are some problems concerning the providing of cybersecurity in Ukraine that concern ambiguity in the definition of the term «cybersecurity», the use of unlicensed software, etc. The article describes the steps of software development, requirements for its use, a brief user's guide is provided. There are also requirements for designing the interface of the software, the software aspects of the development of the snif-fer; the functionalities of the developed software tool are described in the form of items and sub-points of the main and context menu. The functional capabilities of the development of the sniffer allow you to automate the individual functional responsibili-ties of the system administrator. It also provides the ability to control the whole process of data transfer in arbitrary software. It is noted that the software can intercept the input data of 32-bit applications running under the
Разработка и использование снифера как средства обеспечения безопасности ТСР соединений
The development and usage of the snifer as a safety method of ТСР - connectivity
Keywords: кібербезпека; сніфер; захист мережевих даних; TCP з’єднання; системні програмні засоби; прикладні програмні засоби; мережевий трафік; уніфікація; аналізатор трафіку; програмно-апаратний пристрій; кибербезопасность; снифер; защита сетевых данных; TCP соединения; cybersecurity; sniffer; network data protection; TCP connection